Effectiveness of Lemon Aromatherapy on Nausea and Vomiting in Pregnant Women in the First Trimester at Paguyaman Health Center - Anasthia Agusthian Thaib; Rani Safitri; Addina Khoirurnisa (Journal of Global Research in Public Health, 2024)
Nausea and vomiting are common symptoms in the first trimester or early pregnancy, 50-90% of mothers experience nausea and vomiting in the first trimester. The purpose of this study was to determine the effect of lemon aromatherapy on nausea and vomiting in pregnant women in the first trimester at the Paguyaman Health Center. The research design used was Quasi Experimental with the Pre and Post Test. The sample in this study was 16 pregnant women in the first trimester with the Purposive Sampling technique. The results of the Paired T-test were obtained after administration of lemon aromatherapy, most respondents, namely 13 people (81,2) did not experience nausea and vomiting, and 3 respondents (18,8) experienced nausea and vomiting, the p-value test was 0.003 (<0.005). The conclusion of this study is that there is an effect of aromatherapy (lemon) on nausea and vomiting in pregnant women in the first trimester. It is recommended that this aromatherapy method (lemon) be used as a reference in midwifery care for pregnant women, especially to reduce nausea and vomiting.